Shea butter nourishes opportunities for African women - Rebecca Moudio (Africa Renewal, 2013)
In a fancy Manhattan hotel in New York, women in colorful traditional African gowns make their way to one of the conference rooms. Their outfits provide a fascinating contrast to the grey and black business suits surrounding them. The crowd is diverse, but is gathered because of one thing: shea butter that comes from an African nut and is used in cosmetics as a lotion or moisturizer.